Relative expression of IL-10 and TNF-α mRNA of kidney and spleen tissues of rat with and without mammary tumor after exposed to alternating current electric field - Nafisa Khoirun Widiasri; Anysah Nur Fauziyah; Firman Alamsyah; Rarastoeti Pratiwi (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Cancer therapy based on alternating current electric field exposure, Electro-Capacitive Cancer Therapy (ECCT), has been pre-clinically tested for its effectiveness in breast tumor inhibition. However, concerns regarding the safety of electric field (EF) exposure to vital organs have been raised. In the kidney and spleen, IL-10 and TNF-α play roles in the response to inflammation. Objective: This research aimed to evaluate the safety of electric field exposure to vital organs, by assessing the expression of IL-10 and TNF-α mRNA in the kidney and spleen of rats, both with and without breast tumors. Methods: Female rats were divided into four groups; non-induction-non-therapy (NINT), non-induction-therapy (NIT), induction-non-therapy (INT), and induction-therapy (IT). Rats were induced by 7,12-dimethylbenz[a]anthracene (DMBA) at a dosage 20 mg/Kg body weight and exposed to electric fields for 10 hours, followed by a 2-hour rest period. Total RNA from the kidney and spleen was isolated, cDNA was synthesized by reverse transcription PCR, and analysis of IL-10 and TNF-α mRNA expression was performed by RT-qPCR method. Data were analyzed using the Livak formula, GraphPad Prism 9.0 software, and significance test ANOVA (α = 0.05). Results: Alternating current electric field exposure had no effects on the expression of TNF-α and IL-10 mRNA in the kidney and spleen of rats. Specifically, no effect was observed on TNF-α mRNA expression in all groups, and there was no effect on IL-10 mRNA expression in the spleen. Only the INT group showed a significant increase in IL-10 mRNA expression in the kidney (p < 0.05). Conclusion: Exposure of an alternating current electric field did not affect the relative mRNA expression of TNF-α and IL-10 in the kidneys and spleen of rats.